MgO nanoparticles dispersion effects in electro optical parameters of 5CB nematic liquid crystal. Issue 1 (3rd July 2021) - Vafaei, R.; Vahedi, A.; Tajalli, H.; Zakerhamidi, M. S.
Abstract: MgO nanoparticles (NPs) have been dispersed in pure 5CB in three various concentrations. It was found that by incrementing NPs concentration, dielectric permittivities ( ε ∥ and ε ⊥ ) and dielectric anisotropy (Δ ε ) continuously decrease. Real dielectric permittivities of pure and doped liquid crystals in terms of frequency in the range 50–500Hz were obtained. The influence of nano doping on physical and optical parameters, i.e. threshold voltage, ac electric conductivity, phase transition temperature, light transmission, splay elastic constant and refractive index anisotropy was investigated. The temperature-dependent dielectric properties have been improved in the frame of a novel six-parameter dielectric permittivity model.